Effect of a BSHP process on clinical work ability of nurses in a children's cardiac intensive care unit - Ma, Fangyan; Shi, Aiguo; Bian, Lanzheng; Li, Mei; Li, Mingxiong; Xu, Banghong (Frontiers in Pediatrics, 2023)
Background: Nurse shift change is the key step to ensuring the integrity, dynamics, and continuity of clinical nursing in intensive care units. Objectives: To evaluate the effect of a bedside shift handover process (BSHP) on the clinical work ability of first-line clinical nurses in a children’s cardiac intensive care unit (CICU). Methods: This quasi-experimental study was performed on the first-line clinical nurses working in a pediatric CICU at Children’s Hospital of Nanjing Medical University between July and December, 2018. Participants were trained by the BSHP. This article is based on the STROBE checklist. Results: A total of 41 nurses were trained, with 34 women. The nurses in the intensive care unit showed significantly improved clinical work ability, including the ability to assess illness/find problems, master professional knowledge, standardized hands-on ability, ability to express communication, strain handling capacity, and humanistic care and accomplishment (all P < 0.05), after training. Conclusion: BSHP might improve the clinical work ability for pediatric CICU nurses through a standardization shift handover. The traditional oral shift change in CICU can easily cause an information distortion, and it is difficult or even impossible to arouse the nurses’ enthusiasm. This study suggested that BSHP might be an alternative shift change process for pediatric CICU nurses.